Impact of GDD on phenology of mango (Mangifera indica) - KANZARIA, DILIP; CHOVATIA, RAVJI; POLARA, NITESH; VARU, DEVSHI (The Indian Journal of Agricultural Sciences, 2015)
The present investigation was undertaken to see the influence of Heat Units on the phenological changes in mango (Mangifera indica L.) cultivars under South Saurashtra agro-climatic conditions at Department of Horticulture, Junagadh Agricultural University, Junagadh during year 2012-13 and 2013-14. The treatments were comprised of three locations, viz. Junagadh (L1), Talala (L2) and Dhari (L3) and three commercial important mango varieties, viz. Kesar (V1), Alphonso (V2) and Rajapuri (V3). The experiment was laid out in Randomized Block Design with Factorial concept (FRBD) and replicated four times. Significantly the minimum days for bud differentiation (166.46 days with 1402.94 GDD), early flower initiation (73.04 days with 420.36 GDD) and short flowering span (60.42 days with 444.69 GDD) was observed at Talala location. Among the varieties, early flower initiation (75.83 days and 381.04 GDD) and compact flowering span (60.63 days with 382.84 GDD) was observed in Kesar. The minimum days for fruit set (24.33 with 131.61 GDD), pea stage (20.63 with 173.10 GDD), marble stage (42.96 days and 446.48 GDD), egg stage (69.17 days and 809.13 GDD) and maturity (93.75 days with 1272.06 GDD) were rerecorded at Talala location, whereas early fruit set (24.00 days with 100.63 GDD), pea stage (20.83 days with 144.47 GDD), marble stage (43.67 days and 361.66 GDD), egg stage (70.54 days and 694.79 GDD) and maturity (95.88 days and 1062.71 GDD) was also noted in Kesar. The highest fruit set at pea (13.84%), marble (1.57%), egg stage (0.31%) and fruit retention (1.39%) were recorded at Talala. Among the varieties, the maximum fruit set at pea stage (13.84%) was recorded in Alphonso, while it was the maximum at marble (1.60%), egg stage (0.32%) and fruit retention (1.32%) in Kesar. However, the maximum numbers of fruits/tree were recorded at Talala location (335.21) in Alphonso variety (344.33).